Privacy Preserving Technique for Data Storage in Cloud Computing - Kaur, Jagpreet; Goel, Nitin (Asian Journal of Engineering and Applied Technology, 2018)
With the emergence of Cloud computing, the traditional computing process has undergone a sea change. Cloud Computing has been proving to be a boon for IT industries in terms of its ability to provide cost effective, power efficient, extensible and pliable computing. Because of its substantial flexibility, Cloud Computing has become an escalate platform for the services of next generation. But inspite of all the advantages, security and privacy of the data being shared on Cloud remains a cause of concern for the users as well as service providers. This paper proposes a ‘Tortoise technique’ aiming to provide more privacy to user’s data without any kind of security threats from outside. As a part of the technique, reduced data is sent to cloud instead of the original encrypted data. We observed an improvement to an order of 2n in the security of data with the help of the proposed technique.